Evaluating tastes and aromas of wine: a peek inside the "black box". Issue 3 (12th August 2014) - B. Rinaldo, Shannon; F. Duhan, Dale; Trela, Brent; Dodd, Tim; Velikova, Natalia
Abstract : Purpose: – Wine tasting is an integral method for engaging consumers. Producers go to great lengths to educate consumers on evaluating quality based on taste and aroma. Understanding the sensory and perceptual processes of wine tasting may offer insight into how consumers at different levels of wine expertise use their senses to evaluate wine. Design/methodology/approach: – This study used functional near-infrared spectroscopy to examine processing in the frontal lobe of the brain during wine tasting and aroma evaluation. Sixty subjects evaluated the tastes and aromas of wine samples with various levels of sweetness, whereas 16 defined areas of their frontal lobes were measured with functional near infrared measurement. Findings: – The subjects' orbitofrontal cortices were activated during both olfaction (smelling) and tasting. Further, larger areas of the frontal lobes showed significant activation during the olfaction task than during the tasting task. The level of the subjects' wine knowledge did not predict differences in neural processing when participants evaluated aroma of wine; however, subjects with higher wine knowledge did show significantly higher activation in specific frontal lobe regions when tasting. Differences in levels of product involvement among the subjects were not significant for the tasting task, but were significant for the olfaction task. Originality/value: – Developing a better understanding of the biological processes involved in tasting may lead to understanding the differences in consumer preferences for wine. This, in turn, may assist tasting room managers to adjust their tasting procedure to be tailored to consumer-specific needs.